2017
DOI: 10.1038/s41431-017-0043-9
|View full text |Cite
|
Sign up to set email alerts
|

Points to consider for laboratories reporting results from diagnostic genomic sequencing

Abstract: Although NGS technologies are well-embedded in the clinical setting for identification of genetic causes of disease, guidelines issued by professional bodies are inconsistent regarding some aspects of reporting results. Most recommendations do not give detailed guidance about whether variants of uncertain significance (VUS) should be reported by laboratory personnel to clinicians, and give conflicting messages regarding whether unsolicited findings (UF) should be reported. There are also differences both in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 19 publications
2
110
0
Order By: Relevance
“…Conversely, the policy of half of the Belgian CMGs that allow an opt-out from IFs is supported by Vears et al's points to consider for laboratories and by the CCMG position statement which states that "competent adults should be given the option prior to testing to receive (or not receive) incidental findings unrelated to the primary test indication." [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the policy of half of the Belgian CMGs that allow an opt-out from IFs is supported by Vears et al's points to consider for laboratories and by the CCMG position statement which states that "competent adults should be given the option prior to testing to receive (or not receive) incidental findings unrelated to the primary test indication." [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical exome sequencing (ES), variants in diagnostically unrelated but known disease genes can be unintentionally revealed or actively pursued as, respectively, incidental findings (IFs) and secondary findings (SFs) [1][2][3]. Incidental and secondary findings are the subject of various reporting guidelines and policy documents, for instance in Europe, the US and Canada [1][2][3][4][5][6][7]. Ethical arguments, especially concerning autonomy, non-maleficence and beneficence, have been frequently cited for reporting these results or not doing so [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…30 For this reason, authors have suggested focusing on UF that are relevant to the health of patients, rather than actionability, might be more appropriate as a threshold for reporting, provided consent from the patient has been obtained. 30 Approximately, one-third of the forms indicated they offer to return SF. The relatively high proportion of laboratories/clinics that return SF could be due to the fact that many of the forms in our sample are from laboratories based in the United States where laboratories may be more likely to follow the ACMG recommendations compared with those in other parts of the world.…”
Section: Ayuso Et Al or A Number Of Professional Bodies That Have Dementioning
confidence: 99%
“…1,7,8 Although from a justice perspective, ideally all laboratories would provide the same service, some authors have suggested that if laboratories are going to offer this service, it should be performed as an additional, secondary analysis. 30…”
Section: Ayuso Et Al or A Number Of Professional Bodies That Have Dementioning
confidence: 99%
“…The question, then, is whether laboratories should (systematically) reanalyze stored genetic data. For the CG context, periodic reanalysis has been recommended in nondiagnostic cases, although a recent interdisciplinary working group came to the consensus that laboratories have no obligation to routinely analyze data [68,70,73,74]. In the MP context, laboratories are encouraged to set up clear and appropriate policies, but discussion in literature, let alone consensus in the MP context, are lacking on what would be an appropriate reanalysis and recontact policy [10,23,[75][76][77][78].…”
Section: S Vos Et Almentioning
confidence: 99%